Carbon-sequestering abilities of pineapple leaf residue chars and their decomposition in a tropical peat - Lee, Yit Leng (2013)
Oxidation of peat in combination with biomass burning on dry surface peat could result in substantial carbon emissions to the atmosphere contributing to climate change processes. Conversion of biomass into biochar is able to reduce CO2 levels in the atmosphere by sustainably sequestering C. Field burning of pineapple leaf residues (PLR) on peat is a traditional practice to prepare land for cultivation. However, during the open burning not all of the PLR are converted into biochar but ash will also be produced. Biochar produced under controlled combustion is hypothesized to have better yield and quality, thereby better in sequestering C than the biochar produced from the open burning. The study was undertaken to compare the chemical properties and yields of PLR biochar produced by field burning (CF) with that produced by a partial combustion of air-dried PLR in a furnace (CL). Futhermore, the biochar decomposition with and without added fertilizer in the peat were determined. Biochar produced by the CF and the peat samples were collected from Peninsula Plantation, Johor, Malaysia. The CL biochar was produced by partially combusting the PLR at 340°C for 3 hours in a furnace. Standard procedures were used to determine the chemical properties of biochars produced by CL and CF. The refractory nature of biochar samples were determined by analyzing the lignin content and C/N ratio. The chemical functional groups of PLR and biochar samples were identified using Fourier Transform Infrared Spectrocopy (FTIR). The decomposition of biochars with and without added fertilizer on the tropical peat over 12 months were determined using the litterbag method. Total C (42.19%), lignin content (55.45%) and yield (5.63%) from CF was found to be significantly lower than CL. Higher total C (53.30%), lignin content (63.34%), and yield (33.71%) from CL as well as the presence of aromatic compounds in the FTIR spectra of the CL biochar suggest that the CL process was better in sequestering C than was the CF process. Although the C/N ratio (20.56) of biochar produced from CL was significantly lower than CF (23.90), the C in the CL biochar was dominated by lignin suggesting that the decomposition of biochar produced from CL would be slow. Decomposition of CL and CF biochars in peat, with and without added fertilizer, fit the three-parameter single exponential decay model. Fertilizer treatment significantly reduced the weight and lignin remainings in the CL and CF biochars after 12 months. The FTIR spectra showed the changes in the functional groups of both biochars over 12 months were most likely the transformation from aliphatic to aromatic functional groups. Total C remaining in the biochar showed an increase in this order: CF + fertilizer (0.25 Mg/ha) < CF (0.31Mg/ha) < CL + fertilizer (2.05 Mg/ha) < CL (2.41 Mg/ha). To sequester C by biochar application, the PLR could be partially combusted in a controlled process rather than by burning in the field.